Assessment and offset of the adverse effects induced by PM2.5 from coal-fired power plants in China. (1st March 2021) - He, Chengyu; Huang, Guohe; Liu, Lirong; Li, Yongping; Zhai, Mengyu; Cao, Rong
Abstract: Coal-fired power plants are major sources of air pollution in China. Primary particulate matter, sulfur dioxide (SO2 ) and nitrogen oxides (NOX ) emitted from coal-fired power plants formed a large amount of PM2.5 and further imposed heavy burdens on human health and socio-economy. Thus, there is a growing need to assess such adverse effects and explore effective approaches to offset them. This study aims to advance an integral framework, covering health impact assessment, economic loss estimation and adverse effects offset, to understand and mitigate the negative effects induced by PM2.5 from coal-fired power plants in China. In detail, an emission-based model recommended by United Nations Environment Program (UNEP) was adopted to link the emissions of coal-fired power plants with premature mortality cases (PMC). Then, the economic losses triggered by PMC (including the integral loss, the macro loss and the direct loss) were assessed from multiple perspectives. After that, two approaches, respectively aiming to identify the key coal-fired power plants and optimize the economic structure, were developed to offset the economic losses. We found that 22, 231 premature mortality cases occurred in China during 2012 due to PM2.5 from coal-fired power plants (accounting for 0.02‰ of the national population). The corresponding integral loss amounted to CNY 17 billion and was equivalent with 0.03‰ of China's GDP in 2012. Emission abatement against key coal-fired power plants had potential to decrease the integral loss by 23.18%. Increasing the self-input coefficient of the chemical industry in Shandong by 0.018% could offset the integral loss. At provincial level, Jiangsu payed the greatest cost in health and economy, and played the vital role in cross-provincial loss. The PMC occurred in Liaoning entailed great economic losses of other provinces, while the total output of Beijing was sensitive to the PMC occurred in other provinces. These results could provide new insights for the rational policy development to ensure the long-term social welfare. Highlights: 22231 premature mortality cases occurred in China during 2012 due to PM2.5 from coal-fired power plants. The integral loss was 53.71 times the direct loss and amounted to CNY 17 billion. Jiangsu payed the greatest healthy and economic costs, and played the vital role in cross-provincial losses. Minor economic structure adjustments could offset the integral loss.